Study of Cosmology and Basic Implications for Islamic Education (Study of Qs Al-Mulk: 3-4 and Qs Al-Furqan: 2) - Assad, Anas (Universitas Muhammadiyah Surakarta, 2023)
This study examines cosmology in the Qur'an, focusing on verses 3-4 of Surah Al-Mulk and verse 2 of Surah Al-Furqan. This study is library research. Data sources are obtained by reviewing books, articles, journals, theses, and dissertations related to this study. The main objective is to analyze the basic implications of understanding cosmology in the Qur'an in Islamic education.